2015
DOI: 10.1016/j.neuroscience.2015.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Perineural capsaicin induces the uptake and transganglionic transport of choleratoxin b subunit by nociceptive c-fiber primary afferent neurons

Abstract: The distribution of spinal primary afferent terminals labeled transganglionically with the choleratoxin B subunit (CTB) or its conjugates changes profoundly after perineural treatment with capsaicin. Injection of CTB conjugated with horseradish peroxidase (HRP) into an intact nerve labels somatotopically related areas in the ipsilateral dorsal horn with the exceptions of the marginal zone and the substantia gelatinosa, whereas injection of this tracer into a capsaicin-pretreated nerve also results in massive l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…Other laboratories, however, offered evidence against this mechanism of translaminar central sprouting of A-fibers after nerve lesions, interpreting these findings as the result of a phenotypic switch in Cafferents, which after injury would express in their membrane the GM1 monoganglioside, and hence the ability to take up and transport CTB (Tong et al (1999). A variety of more recent tracing studies supported this contention (Santha et al 2003;Shehab et al 2003;Woodbury et al 2008;Oszlacs et al 2015). The only comparable study in the IoN territory, which studied the terminals from genetically labeled, parvalbumin-expressing A-neurons of the trigeminal ganglion, also failed to support the thesis of reactive sprouting in lamina II of Sp5c following inflammation or transection of the nerve (Zhang et al 2015).…”
Section: Effects Of Input Alteration On the Dual Innervation Of Sp5cmentioning
confidence: 99%
“…Other laboratories, however, offered evidence against this mechanism of translaminar central sprouting of A-fibers after nerve lesions, interpreting these findings as the result of a phenotypic switch in Cafferents, which after injury would express in their membrane the GM1 monoganglioside, and hence the ability to take up and transport CTB (Tong et al (1999). A variety of more recent tracing studies supported this contention (Santha et al 2003;Shehab et al 2003;Woodbury et al 2008;Oszlacs et al 2015). The only comparable study in the IoN territory, which studied the terminals from genetically labeled, parvalbumin-expressing A-neurons of the trigeminal ganglion, also failed to support the thesis of reactive sprouting in lamina II of Sp5c following inflammation or transection of the nerve (Zhang et al 2015).…”
Section: Effects Of Input Alteration On the Dual Innervation Of Sp5cmentioning
confidence: 99%
“…Although the specific binding of CTB to the GM1 ganglioside is well established [14,15], a possible role of this ganglioside species in sensory functions remained unclear. Electron microscopic histochemical studies demonstrated a conspicuous membrane localization of CTB-HRP [104,107,108] and suggested its association with membrane lipid rafts [104,107]. Inferred from the morphological observations, these findings indicated a putative role of GM1 ganglioside in the function of nociceptive primary sensory neurons possibly through interaction with membrane lipid microdomains/lipid rafts [104,107,108] (vide infra).…”
Section: Effect Of Peripheral Nerve Lesions On the Distribution Of Gamentioning
confidence: 80%
“…This observation has mainly been based on the utilization of the retrograde and transganglionic neuronal tracer CTB-HRP. As mentioned above, normally it is mainly taken up and transported retrogradely by large diameter myelinated A-fibres and labels the somatotopically related areas of the dorsal horn (laminae I and III-VI) (LaMotte et al, 1991;Oszlács et al, 2015;Robertson and Grant, 1985;Shehab and Hughes, 2011;Trojanowski et al, 1982). However, 2 weeks after a peripheral nerve lesion CTB-HRP labelling was apparent not only in the deeper layers of the dorsal horn but also in lamina II, a region which normally receives only C-fibre input (Lekan et al, 1996;Shehab et al, 2004;Shortland et al, 1997;Woolf et al, 1992;Woolf et al, 1995).…”
Section: Methods For Demonstration Of the Central Projections Of Perimentioning
confidence: 94%